2022
DOI: 10.1039/d1nr07286b
|View full text |Cite
|
Sign up to set email alerts
|

Atomically precise structures of Pt2(S-Adam)4(PPh3)2 complexes and catalytic application in propane dehydrogenation

Abstract: As the bridge between single metal atoms and metal nanoclusters, atomically precise metal complexes are of great significance for the controlled synthesis and catalytic applications at the atomic level. Herein,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Briefly, Pt precursors were prepared firstly via the coordination of K 2 PtCl 4 with the corresponding ligands (1-adamantanethiol and triphenylphosphine) in the presence of phase transfer agent (tetra-n-octylammonium bromide) and NaBH 4 . 43 Subsequently, the resulting metal precursors were loaded on OCNTs (denoted as Pt/CNT) and then annealed at different temperatures of 400, 600, and 800 °C in argon. The asprepared catalysts were denoted as Pt/CNT-400, Pt/CNT-600, and Pt/CNT-800, with the actual Pt loadings of 4.4, 4.7, and 4.6 wt %, as determined by inductively coupled plasma optical emission spectrometer (ICP-OES).…”
Section: Preparation and Characterization Of Catalystsmentioning
confidence: 99%
“…Briefly, Pt precursors were prepared firstly via the coordination of K 2 PtCl 4 with the corresponding ligands (1-adamantanethiol and triphenylphosphine) in the presence of phase transfer agent (tetra-n-octylammonium bromide) and NaBH 4 . 43 Subsequently, the resulting metal precursors were loaded on OCNTs (denoted as Pt/CNT) and then annealed at different temperatures of 400, 600, and 800 °C in argon. The asprepared catalysts were denoted as Pt/CNT-400, Pt/CNT-600, and Pt/CNT-800, with the actual Pt loadings of 4.4, 4.7, and 4.6 wt %, as determined by inductively coupled plasma optical emission spectrometer (ICP-OES).…”
Section: Preparation and Characterization Of Catalystsmentioning
confidence: 99%
“…In the study of catalyst selection, the ability to activate CH bonds is a point that should not be neglected in the selection of catalysts. For the well‐known Cr‐based catalysts [17–21] and Pt‐based catalysts [22–30], for example, each of them has a different way of activating CH bonds, and their ability to activate CH bonds is of course also different. Pt‐based catalysts activate propane CH bonds mainly through adsorption and electron transfer processes.…”
Section: Introductionmentioning
confidence: 99%
“…16 After ligands that provide S and P coordinating atoms to Pt were introduced, the atomic Pt species exhibit a mixed oxidation state of positively charged Pt 2+ and metallic Pt 0 , showing better catalytic performance than Pt in the positively charged Pt 2+ state, with a propane conversion of about 18.3% and propylene selectivity of 93% at 550 °C in PDH. 21 Chen et al also suggested that fully exposed Pt 3 clusters on defect-rich graphene show a unique atomic arrangement where two Pt atoms are connected to the C/O atoms on the support and likely carry a positive charge, while the third Pt atom, bonded solely to other Pt atoms, may be metallic in character. Their experiments showed a high conversion (35.4%) and alkene selectivity (99.0%) for nbutane dehydrogenation at 450 °C compared to single Pt atoms and typical Pt nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Atomically dispersed metal species on metal-oxide supports usually carry positive charges when coordinated to oxygen ions, but sometimes they can remain in a metallic zerovalent state. ,, For instance, as the Pt loading decreases, a dramatic increase in the proportion of positively charged Pt δ+ species was observed on the subnanometer-sized metal clusters over γ-Al 2 O 3 . After ligands that provide S and P coordinating atoms to Pt were introduced, the atomic Pt species exhibit a mixed oxidation state of positively charged Pt 2+ and metallic Pt 0 , showing better catalytic performance than Pt in the positively charged Pt 2+ state, with a propane conversion of about 18.3% and propylene selectivity of 93% at 550 °C in PDH . Chen et al.…”
Section: Introductionmentioning
confidence: 99%